Copenhagen. City of cyclists. Bicycle Account 2002. - (:unkn) unknown (My University, 2003)
Der Bericht enthält zum einen Befragungsergebnisse von Kopenhagener Fahrradfahrern und deren Einstellungen zum Fahrradfahren in ihrer Stadt. Zum anderen werden Schlüsselfaktoren der Fahrradförderung mit den infrastrukturellen und sozio-ökonomischen Verhältnissen in Kopenhagen verglichen. Zusätzlich werden Informationen über laufende Projekte und Initiativen im Bereich Radverkehrsförderung des Jahres 2002 gegeben.

The Bicycle Account is an account for cyclists and the City of Copenhagen, showing the City's record in the field of cycling. The cyclist section of the account consists of a survey in which Copenhagen cyclists describe how they feel about cycling in town. The City section of the account is a kind of stocktaking in which a number of key figures are used to depict conditions which are vital to cyclists. In addition, the target figures indicate the extent to which the Cycle Policy's objectives are being achieved. The Bicycle Account also provides information about the City's projects and initiatives within the field of cycling.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Statistik; Verkehrssicherheit; Radwegenetz; Befragung; Stadtverkehr; Fahrradförderung; Fahrradnutzung; Fahrradinfrastruktur; Radverkehrspolitik